Social Labs and Interreligious Dynamics: A Methodological Breakthrough in Understanding and Countering Extremism - Gamuzza, Augusto; Mavica, Giorgia; Scieri, Alessandra (Italian Sociological Review, 2025)
Against the backdrop of escalating extremism and radicalisation across Europe, traditional methodologies for strengthening counterterrorism and fostering social integration are increasingly limited in addressing the intricacies of these phenomena. This paper focuses on the groundbreaking methodological innovation of Social Labs, conducted with interreligious dialogue networks, as a means of grappling with the multi-dimensional socio-economic and religious factors contributing to radicalisation. Within the sociological paradigm, Social Labs emerge as participatory spaces that facilitate the engagement of religious communities, leaders and interfaith networks in collaborative problem-solving and policy formulation. Drawing on empirical research in Italy, Belgium and the Netherlands, the paper explores the groups working with interreligious dialogue networks within the framework of Social Labs. These tools not only provide an enriched contextual understanding of religious extremism but also foster an environment where localised, community-based solutions can emerge. The Social Lab framework, rooted in participatory action-research, facilitates dynamic exchanges among stakeholders, thereby enhancing the contextualisation of extremism, while also promoting interreligious dialogue. The paper critically evaluates the outcomes of the Social Labs for interreligious dialogue networks, analysing how this methodological innovation yields detailed insights into the socioeconomic and religious underpinnings of radicalisation. More significantly, the paper aims at addressing the efficacy of Social Labs in eliciting local, context-specific strategies in terms of counterterrorism and social cohesion strategies, providing a methodologically innovative pathway for addressing extremism and fostering social integration in a multi-religious society in dialogue.